Immediate loading on fixed implant-supported prosthesis with short implants: short-term report of four cases - Moura, L. B. [UNESP]; Paganelli, O. E.B.; Gabrielli, M. A.C. [UNESP]; Pereira Filho, V. A. [UNESP] (Wiley, 2018)
Short implants are one of the best alternative treatments for atrophic mandibles due to low morbidity and good resolution. The use in posterior mandible is consolidated, however, in edentulous patients is rarely reported. The aim of this article is to present the use of short implants with fixed implant-supported prosthesis and immediate loading in severely resorbed mandibles, in four patients. Four short implants were placed in the anterior mandible in each patient. The initial torque of all implants was higher than 45 N and the mean of resonance frequency analysis was 74.87. The fixed prosthesis was submitted to immediate loading. After 4 years of follow-up there were two implant failures which were replaced by other short implants. All implants remain in function with no signs of perimplantitis or bone loss. The final resonance frequency analysis mean was 78.30 demonstrating adequate stability.
Keywords: atrophy; dental implant; immediate dental implant loading; oral rehabilitation